Arbuscular mycorrhizal fungi and goethite promote carbon sequestration via hyphal-aggregate mineral interactions. (November 2021) - Jeewani, Peduruhewa H.; Luo, Yu; Yu, Guanghui; Fu, Yingyi; He, Xinhua; Van Zwieten, Lukas; Liang, Chao; Kumar, Amit; He, Yan; Kuzyakov, Yakov; Qin, Hua; Guggenberger, Georg; et al.
Abstract: Goethite is known to contribute to the co-precipitation of rhizodeposits and thus benefit carbon (C) sequestration, while arbuscular mycorrhizal fungi (AMF) play significant role in soil organic C (SOC), however, the combined effect is less known. To address this paucity in knowledge, we compared the physicochemical stabilization and microbial mineralization of rhizodeposits from maize ( Zea mays L.) and the rhizosphere priming effect (RPE) in soils with a combination of goethite addition and AMF inoculation. Here, we showed that compared to the control: i) Co-amendment of AMF and goethite resulted in a 0.6-fold decrease of rhizodeposit derived CO2, and a 2.8-fold larger allocation of rhizodeposits into macro-aggregates, most likely due to precipitation by goethite and macro-aggregate formation stimulated by AMF hyphae. Analyses using μ-FTIR confirmed the spatial distribution of polysaccharides overlapped with Fe–O minerals within macro-aggregates, supporting the concomitant processes of rhizodeposit stabilization and aggregate formation via hyphal-aggregate mineral interactions; ii) Inoculation with AMF accelerated SOC turnover by increasing the RPE (by 6.1 mg C kg −1 day −1, 74% increase) and rhizodeposit stabilization (by 6.2 mg C kg −1 soil day −1, 47% increase). The larger soil priming effect stimulated by AMF was associated with several genera including Solirubrobacter, Pseudomonas and Talaromyces, suggesting these hyper-symbionts were involved in nutrient acquisition (mining hypothesis). Our results enabled the comparison between rhizodeposit stabilization versus rhizodeposit and SOC mineralization, and highlighted the contributions of both goethite (abiotic contribution) and AMF (biotic contribution) to C accrual in a soil-plant system. Highlights: AMF and goethite stabilized rhizo-C via mineral-aggregate-hyphae interaction. μ-FTIR confirmed the spatial distribution of polysaccharides overlapped with Fe–O. AMF increased SOM priming via extended hyphae and hyper-symbiont activity. AMF enhanced both rhizo-C stabilization and soil priming and thus faster SOC turnover.